A proposal designed for calibrating the liquidity coverage ratio for Islamic banks. Issue 1 (17th April 2019) - Dolgun, Muhammed Habib; Mirakhor, Abbas; Ng, Adam
Abstract : Purpose: This paper aims to critically investigate the liquidity risk management of Islamic banks and develop an alternative regulatory framework appropriate for liquidity management of these banks. Design/methodology/approach: The specific risk profile of an Islamic bank requires developing a new and more efficient regulatory framework, which relies on risk- sharing and symmetric information among parties. The paper makes a differentiation between small local banks and internationally active Islamic banks and proposes to apply liquidity requirements only for internationally active Islamic banks. Findings: A new proposal for the liquidity coverage ratio (LCR) of Islamic banks is developed in this paper towards mitigating risks and concurrently protecting the interests of investment account holders. Minimum and maximum thresholds are proposed for each liquid asset in this new LCR framework. An alternative liquidity approach is discussed to complement the proposal and several policy options are suggested. Originality/value: As participation banks are exposed to market liquidity and market risks, more high-quality liquid instruments within a risk-sharing regulatory framework may provide the inner adjustment process through which any mismatch regarding maturity, risk, value or linkage with the real economy is corrected systematically. It offers policy implications for regulators, supervisors and international organizations.